Key factors influencing student satisfaction with an online learning platform in a Malaysian Higher Education Institution - Mansor, Aida Azlina; Mohammed Shobri, Nor Diyana; Abd Rashid, Muhammad Hafiz; Jit Singh, Keshminder Singh (Universiti Teknologi Mara Selangor, 2025)
This study investigates the relationships between Information Quality, System Quality, Service Quality, Perceived Usefulness, Perceived Ease of Use, and Cognitive Absorption with student satisfaction towards an online learning platform. The target population comprised undergraduate students from a prominent Malaysian university campus. Using a non-probability convenience sampling method, data were collected from a total of 106 respondents, considered sufficient for the intended correlational analyses. Structured, self-administered questionnaires featuring multiple-choice and Likert-scale items were distributed to capture students’ perceptions across all constructs. The correlation analysis revealed that all six factors are significantly and positively associated with student satisfaction, indicating strong preliminary support for the conceptual framework. All hypotheses were supported, confirming that improvements in these six key areas are likely to contribute to higher levels of satisfaction among students. Grounded in the Technology Acceptance Model (TAM) by Davis (1989), the findings affirm that students’ perceptions of usefulness and ease of use play a crucial role in determining their satisfaction and acceptance of the platform. The findings underscore the importance of delivering high-quality information and services, ensuring system reliability, enhancing perceived usefulness and ease of use, and fostering cognitive engagement to maximise student satisfaction. These results provide practical implications for higher education institutions and platform developers seeking to improve the quality and effectiveness of online learning environments. In summary, the correlation analysis provides strong support for the research framework, highlighting that targeted improvements in the identified factors can significantly enhance students’ online learning experiences. Future research could explore additional constructs or examine potential mediating and moderating effects within this context.